Seasonal Fluctuations of Sympatric Field Murids in Hisar - Saxe, Y; Chandana, S S (Annals of Arid Zone, 2016)
The present paoer reveals a general account of rodents and other animalstrapped during trapping schedule in wire-meshed traps (size 35 cm x 17 cm) inthree different sub-ecological pockets of Hisar area. Lesser bandicoot rat,Bandicota bengalensis; Indian gerbil, Tatero indico and short-tailed male rat,Nesokia indica were the predominant species of district Hisar, Bhiwani andRohtak, respectively. Howevcr, desert gerbils, Meriones hllrrianae weretrapped only from south western part of this area.